2018
DOI: 10.1073/pnas.1717065115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapamycin on growth hormone receptor knockout mice

Abstract: It is well documented that inhibition of mTORC1 (defined by Raptor), a complex of mechanistic target of rapamycin (mTOR), extends life span, but less is known about the mechanisms by which mTORC2 (defined by Rictor) impacts longevity. Here, rapamycin (an inhibitor of mTOR) was used in GHR-KO (growth hormone receptor knockout) mice, which have suppressed mTORC1 and up-regulated mTORC2 signaling, to determine the effect of concurrently decreased mTORC1 and mTORC2 signaling on life span. We found that rapamycin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…Average longevity of GHRKO mice housed at 23°C in the current study resembled the values measured in the previous studies (Bonkowski et al, ; Coschigano, Clemmons, Bellush, & Kopchick, ; List et al, ). Similarly, longevity of WT mice from the same strain housed at 23°C appears to resemble the values recorded in the previous studies (Bonkowski et al, ; Fang et al, ). Interestingly, data available to date suggest that chronic housing at 30°C has no, or very little, impact on the longevity of WT mice from this genetically heterogeneous strain.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Average longevity of GHRKO mice housed at 23°C in the current study resembled the values measured in the previous studies (Bonkowski et al, ; Coschigano, Clemmons, Bellush, & Kopchick, ; List et al, ). Similarly, longevity of WT mice from the same strain housed at 23°C appears to resemble the values recorded in the previous studies (Bonkowski et al, ; Fang et al, ). Interestingly, data available to date suggest that chronic housing at 30°C has no, or very little, impact on the longevity of WT mice from this genetically heterogeneous strain.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…GHRKO mice are GH‐resistant, small, obese, hypoinsulinemic, and highly insulin sensitive. We have previously reported that at 23°C, GHRKO mice had improved glucose metabolism indicated by lower fasting glucose, improved glucose clearance (measured by glucose tolerance test [GTT]), and insulin sensitivity (measured by insulin tolerance test [ITT]) compared to wild‐type mice (Bonkowski et al, ; Bonkowski, Rocha, Masternak, Al Regaiey, & Bartke, ; Fang et al, ). Here, glucose homeostasis was examined at 13 months of age after housing at 30°C for approximately 1 year postweaning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mTOR promotes growth and aging in C. elegans [167], D. melanogaster [168], S. cerevisiae [169], as well as in mice [170,171] and rat [172,173] models. Further, it modulates glucose and lipid metabolism [174,175]. Rapamycin prevents insulin resistance in humans [176], reduces insulin resistance in hyperinsulinemia rats [177,178], and normalizes glucose metabolism in diabetic mice [179,180].…”
Section: Rapamycinmentioning
confidence: 99%
“…In fact, many of these diseases have been associated with dysregulation of mTOR signaling, importantly through imbalanced dietary intake. 7e9 More evidence for the role of diet in regulating mTOR signaling comes from studies of calorie restriction, which have been shown to extend life span, 10 in a diverse array of eukaryotes ranging from yeasts to humans. 11,12 Therefore, gaining a deeper understanding of mTOR's role and function in these poorly defined processes is critical to understanding disease pathogenesis in tissues where mTOR plays a central role.…”
mentioning
confidence: 99%